A study of the maintenance management at Kolej Komuniti in Selangor / Muhammad Hafiz Mohd Salleh - Mohd Salleh, Muhammad Hafiz (Faculty of Architecture, Planning and Surveying, 2013)
The preliminary study had indicated the maintenance system that practised in Malaysian building that due to the inadequate implement of the maintenance management system in the building. Government overcomes these poor maintenance cultures between the Malaysian by increase the knowledge and awareness about the important of the building maintenance. Thus, this research is present about the implementation of the maintenance management at the Kolej Komunit in Selangor. The objectives of this study is to study the maintenance management system at Kolej Komuniti and to identify the problem arise in the maintenance management that practised at Kolej Komuniti. The selected case study building that involved in this study is Kolej Komuniti Klang (KKK) and Kolej Komuniti Kuala Langat (KKKL). To conducting the study about the maintenance management system at Kolej Komuniti building, the respondents that involved in this study are students and staff in Kolej Komuniti. Literature reviews carried out via secondary data collected from references books, journals, newspaper, magazines, conference papers, and others. By using this secondary data, it helps to know and give better understanding about maintenance management. Besides, it helps the researcher to find the relevant and related ideas according the topic. Questionnaire survey conducted to obtain information and opinion about the condition of the facilities provided and quality of maintenance management. One hundred and thirty (130) respondent was gave their feedback on this study as its enough to generate the data. All the data and information that have been collected through interview, questionnaires and literature review need to be organized, summarized and analysed. Result was analysed and then presented in graph, table, pie charts and others. From the result, quality condition of facilities describes that the highest vote of respondent at agree categories, where we can interpret that they disagree about the quality of maintenance management in the building. Lastly, increase and built up the knowledge about the building maintenance management towards the society is the best suggestion to make sure the building maintenance management can be perform effectively. According to the result, building maintenance management is important to ensure the structure and facilities in fit to use.